DNA sequence and translational product of a new nodulation-regulatory locus: syrM has sequence similarity to NodD proteins. - Barnett, M J (1990)
Rhizobium meliloti nodulation (nod) genes are expressed when activated by trans-acting proteins in the NodD family. The nodD1 and nodD2 gene products activate nod promoters when cells are exposed to plant-synthesized signal molecules. Alternatively, the same nod promoters are activated by the nodD3 gene when nodD3 is carried in trans along with a closely linked global regulatory locus, syrM (symbiotic regulator) (J. T. Mulligan and S. R. Long, Genetics 122:7-18, 1989). In this article we report the nucleotide sequence of a 2.6-kilobase SphI fragment from R. meliloti SU47 containing syrM. Expression from this locus was confirmed by using in vitro transcription-translation assays. The open reading frame encoded a protein of either 33 or 36 kilodaltons whose sequence shows similarity to NodD regulatory proteins.